Soft magnetic alloy, soft magnetic alloy ribbon, soft magnetic alloy powder, and magnetic component

CN115148444BActive Publication Date: 2026-10-27TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210310189.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-24
Filing Date
2022-03-28
Publication Date
2026-10-27
Estimated Expiration
2042-03-28

AI Technical Summary

Benefits of technology

[0006]发明所要解决的技术问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115148444B_ABST
    Figure CN115148444B_ABST
Patent Text Reader

Abstract

Provided is a soft magnetic alloy or the like that is a magnetic component having a good temperature characteristic of core loss. The soft magnetic alloy contains Fe. The soft magnetic alloy includes crystallites and an amorphous phase present around the crystallites. The total area ratio of the crystallites in a cross section of the soft magnetic alloy is 40% or more and less than 60%. The average thickness of the amorphous phase is 3.0 nm or more and 10.0 nm or less. The standard deviation of the thickness of the amorphous phase is 10.0 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a soft magnetic alloy, a soft magnetic alloy strip, a soft magnetic alloy powder, and a magnetic component. Background Technology

[0002] Patent document 1 discloses a soft magnetic alloy with high crystallinity, in which the crystal grain size of the nanocrystals and the average thickness of the amorphous phase are set within a specific range, and the average Fe concentration of the amorphous phase near the surface of the nanocrystals is lower than the average Fe concentration of the nanocrystals.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent No. 6482718 Summary of the Invention

[0006] The technical problem that the invention aims to solve

[0007] The purpose of this invention is to provide a soft magnetic alloy or the like for obtaining magnetic components with good temperature characteristics of core loss.

[0008] Technical solutions for solving technical problems

[0009] To achieve the above objectives, the soft magnetic alloy of the present invention is a soft magnetic alloy containing Fe.

[0010] The soft magnetic alloy comprises microcrystals and an amorphous phase present around the microcrystals.

[0011] The total area ratio of the microcrystals in the cross-section of the soft magnetic alloy is more than 40% and less than 60%.

[0012] The average thickness of the amorphous phase is above 3.0 nm and below 10.0 nm, and the standard deviation of the thickness of the amorphous phase is below 10.0 nm.

[0013] The average particle size of the microcrystals can also be below 15.0 nm.

[0014] It may also contain M,

[0015] M can also be one or more selected from Nb, Hf, Zr, Ta, Mo, V, Ti, and W.

[0016] The total content of M can also be above 3.5 at% and below 10.0 at%.

[0017] It may also contain P.

[0018] The content of P can also be greater than 0 and less than 6.0 at%.

[0019] It may also contain Cu.

[0020] The Cu content can also be greater than 0 and less than 3.0 at%.

[0021] It may also contain Co.

[0022] The Co content can also be greater than 0 and less than the Fe content.

[0023] The soft magnetic alloy strip of the present invention comprises the above-mentioned soft magnetic alloy.

[0024] The soft magnetic alloy powder of the present invention comprises the above-mentioned soft magnetic alloy.

[0025] The first magnetic component of the present invention is formed by stacking the aforementioned soft magnetic alloy strips. The second magnetic component of the present invention is formed by winding the aforementioned soft magnetic alloy strips. The third magnetic component of the present invention comprises the aforementioned soft magnetic alloy powder. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of a soft magnetic alloy.

[0027] Figure 2 This is a schematic diagram of a soft magnetic alloy.

[0028] Figure 3 This is a schematic diagram of the single-roller process.

[0029] Figure 4 It is a graph showing the rate of change of core loss at temperature with 30°C as the reference.

[0030] Explanation of symbols:

[0031] 1… Soft magnetic alloy

[0032] 11…microcrystals

[0033] 13…Amorphous phase

[0034] 31… Nozzle

[0035] 32…molten metal

[0036] 33…rollers

[0037] 34… Soft magnetic alloy strip

[0038] 35…chamber Detailed Implementation

[0039] Hereinafter, embodiments of the present invention will be described using the accompanying drawings.

[0040] The soft magnetic alloy of this embodiment is a Fe-containing soft magnetic alloy, wherein the soft magnetic alloy comprises microcrystals and an amorphous phase present around the microcrystals.

[0041] The total area ratio of the microcrystals in the cross-section of the soft magnetic alloy is more than 40% and less than 60%.

[0042] The average thickness of the amorphous phase is above 3.0 nm and below 10.0 nm, and the standard deviation of the thickness of the amorphous phase is below 10.0 nm.

[0043] The soft magnetic alloy of this embodiment, by having the above-described structure, can achieve excellent temperature characteristics. In particular, it can achieve excellent temperature characteristics for both the soft magnetic alloy strip having the above-described soft magnetic alloy and the magnetic component containing the soft magnetic alloy strip.

[0044] Currently, soft magnetic alloys containing microcrystals and an amorphous phase existing around the microcrystals are known. Furthermore, it is known that the magnetic anisotropy of the microcrystals varies with the temperature of the soft magnetic alloy.

[0045] The inventors have discovered that by controlling the total area ratio of the microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness within the aforementioned specific ranges, temperature characteristics are improved. By controlling these parameters within the aforementioned specific ranges, the effective changes in magnetic anisotropy caused by temperature variations are offset, thus improving temperature characteristics.

[0046] The measurement methods for the above parameters are explained below.

[0047] In this embodiment, a soft magnetic alloy is observed, and various parameters are calculated based on the obtained images. A transmission electron microscope (TEM) is used for the observation of the soft magnetic alloy. The method using TEM will be described below.

[0048] There are no particular limitations on the evaluation methods when using TEM. For example, bright-field observation and high-resolution observation methods can be cited.

[0049] In this embodiment, to accurately evaluate the shape of the microcrystals, the thickness of the sample used for TEM observation (hereinafter referred to as the TEM sample) is thinner than usual. Specifically, the thickness of a typical TEM sample is about 80 to 100 nm, while in this embodiment it is set to less than 20 nm. There are no particular limitations on the method for preparing the TEM sample; for example, a focused ion beam scanning electron microscope (FIB-SEM) can be used. When preparing the TEM sample using a soft magnetic alloy ribbon, the TEM sample is prepared by grinding any side of the soft magnetic alloy ribbon perpendicular to the thickness direction.

[0050] When the TEM sample is thick, the total area ratio of the crystallites sometimes appears larger compared to when the TEM sample is thin. Furthermore, when the TEM sample is thick, multiple crystallites may overlap in the thickness direction, sometimes appearing as a single crystallite. In such cases, the thickness of the amorphous phase cannot be accurately evaluated. In this embodiment, by reducing the thickness of the TEM sample, the aforementioned parameters can be accurately evaluated. Alternatively, the thickness of the TEM sample can also be evaluated using focused-beam electron diffraction (CBED) or electron energy-loss spectrophotometry (EELS), or by direct observation of the TEM sample.

[0051] There are no particular limitations on the size and magnification of the image obtained by TEM. The image size only needs to completely encompass the size of 10 or more microcrystals, preferably 30 or more microcrystals. The magnification of the image obtained by TEM only needs to be sufficient to measure the aforementioned parameters. Specifically, it should be in the range of 100,000 to 1,000,000 times.

[0052] like Figure 1 As illustrated, the soft magnetic alloy 1 comprises microcrystals 11 and an amorphous phase 13 present around the microcrystals 11. Furthermore, Figure 1 And as will be discussed later Figure 2 This is a schematic diagram used to illustrate the measurement methods for each parameter. Figure 1 And as will be discussed later Figure 2 It does not reflect the actual shape of the microcrystal 11 or the actual shape of the amorphous phase 13.

[0053] The ratio of the total area of ​​microcrystal 11 to the area of ​​the image is the ratio of the total area of ​​the microcrystal.

[0054] The thickness of the amorphous phase 13 will be explained below. In calculating the thickness of the amorphous phase 13, only the thickness of the amorphous phase 13 located between the microcrystals 11 from which the whole can be observed is calculated. Figure 1 In the image, the thickness of the amorphous phase 13 between the lower right microcrystal 11 and other microcrystals 11 is not calculated because the lower right microcrystal 11 is not included in the image as a whole.

[0055] For each microcrystal 11 that can be observed as a whole, the centroid 11g is calculated. Then, a virtual line is drawn connecting the two centroids 11g contained in any two microcrystals 11 to each other. However, if the virtual line connecting the two centroids 11g to each other passes through microcrystals 11 other than the two microcrystals mentioned above (including microcrystals 11 that cannot be observed as a whole), no virtual line is drawn.

[0056] exist Figure 1 In the diagram, for each individual microcrystal 11 that can be observed as a whole, no virtual line is drawn connecting the upper-left microcrystal 11 and the upper-right microcrystal 11. This is because when drawing a virtual line, it passes through the microcrystal 11 located between the two microcrystals 11. Conversely, for each individual microcrystal 11 that can be observed as a whole, virtual lines are drawn connecting the two microcrystals 11 to each other for combinations other than the combination of the upper-left and upper-right microcrystals 11. This is because, as... Figure 1 As shown, even when drawing virtual lines, they do not pass through microcrystals 11 other than the two microcrystals 11.

[0057] exist Figure 2 The example includes two microcrystals 11 in a soft magnetic alloy 1 and connected by a virtual line. The point where the virtual line and the outer periphery of the microcrystal 11 intersect is designated as endpoint 11e. Then, the length of the line segment on the virtual line that connects the endpoints 11e to each other is designated as the thickness of the amorphous phase 13 between the two microcrystals 11.

[0058] Then, for all the virtual lines contained in the image, the thickness of amorphous phase 13 is calculated. Then, the average thickness of amorphous phase 13 is calculated by averaging all the thicknesses of amorphous phase 13. Additionally, the standard deviation of the thicknesses of all amorphous phase 13 contained in the image is calculated based on their respective thicknesses.

[0059] Specifically, the number of virtual lines, i.e., the number of thicknesses, is set as n, and the thickness of each amorphous phase is set as x1, x2, ... x. n Let the average thickness of amorphous phase 13 be μ, which is calculated using the following formula.

[0060]

[0061] At this point, the overall variance σ of the thickness of the amorphous phase 13 is calculated using the following formula. 2 .

[0062]

[0063] Then, σ 2 The positive square root of σ becomes the standard deviation σ of the thickness of the amorphous phase 13.

[0064] The type of microcrystals 11 in this embodiment is not particularly limited. Microcrystals 11 can also be nano-sized crystals with α-Fe as the main component. Specifically, microcrystals 11 may contain only α-Fe, or they may contain one or more elements selected from X1, X2, M, B, P, Si, and Cu, in addition to α-Fe. For example, microcrystals 11 may also contain Si and / or Co. The content of one or more elements selected from X1, X2, M, B, P, Si, and Cu in microcrystals 11 is not particularly limited. Furthermore, the average particle size of microcrystals 11 is preferably 15 nm or less. This is because when the average particle size of microcrystals 11 is small, the effective magnetic anisotropy variation caused by temperature changes is reduced, and the temperature characteristics are improved.

[0065] There are no particular limitations on the composition of the soft magnetic alloy in this embodiment, except for the presence of Fe.

[0066] The soft magnetic alloy of this embodiment may also contain M. M is selected from one or more of Nb, Hf, Zr, Ta, Mo, V, Ti, and W. M may also be selected from one or more of Nb, Hf, Zr, Ta, Mo, V, and W. By containing M, the temperature characteristics are easily improved.

[0067] The total content of M can be 0 or more and less than 10.0 at%, greater than 0 and less than 10.0 at%, or greater than 3.5 at% and less than 10.0 at%. The lower the M content, the easier it is to increase the particle size of the microcrystals 11. With an increased particle size of the microcrystals 11, effective magnetic anisotropy tends to increase, and temperature characteristics tend to deteriorate. When the M content exceeds 10.0 at%, the thickness of the amorphous phase 13 tends to increase, and the average thickness of the amorphous phase tends to exceed 10.0 nm. When the average thickness of the amorphous phase exceeds 10.0 nm, temperature characteristics deteriorate.

[0068] The soft magnetic alloy of this embodiment may also contain P. Moreover, the content of P may be greater than 0 and less than 6.0 at%. By keeping the content of P within the above range, it is easy to appropriately control the composition of the amorphous phase 13, and it is easy to control the average thickness of the amorphous phase 13 and the standard deviation of the thickness of the amorphous phase 13 within the above range.

[0069] The soft magnetic alloy of this embodiment may also contain Cu. Furthermore, the Cu content may be greater than 0 and less than 3.0 at%. When the Cu content is within the above range, crystallization 11 is easily and uniformly grown when it is formed in the soft magnetic alloy. As a result, the average thickness of the amorphous phase 13 and the standard deviation of the thickness of the amorphous phase 13 can be easily controlled within the above range.

[0070] The soft magnetic alloy of this embodiment may also contain Co. Furthermore, the Co content may be greater than 0 and less than or equal to the Fe content. Specifically, the value of the Co content divided by the Fe content may be greater than 0 and less than or equal to 1.0. By containing Co in the soft magnetic alloy, the properties can be improved without altering the microstructure of the soft magnetic alloy.

[0071] The composition of the soft magnetic alloy of this embodiment will be described in more detail. The soft magnetic alloy of this embodiment may also have a composition of (Fe...) (1-(α+β)) ×1α×2β) (1-(a+b+c+d+e)) M a B b P c Si d Cu e Soft magnetic alloys whose main components are composed of (atomic ratio),

[0072] X1 is selected from one or more of Co and Ni.

[0073] X2 is selected from one or more elements including Al, Mn, Ag, Zn, Sn, As, Sb, Cr, Ga, Bi, N, O, C, S, and rare earth elements.

[0074] M is selected from one or more of Nb, Hf, Zr, Ta, Mo, V, Ti, and W.

[0075] It can also be

[0076] 0≤a≤0.1500,

[0077] 0≤b≤0.2000,

[0078] 0≤c≤0.2000,

[0079] 0≤d≤0.2000,

[0080] 0≤e≤0.0400,

[0081] 0.7000≤1-(a+b+c+d+e)≤0.9000,

[0082] α≥0,

[0083] β≥0,

[0084] 0≤α+β≤0.70.

[0085] The components of the soft magnetic alloy of this embodiment will be described in detail below.

[0086] M is selected from one or more of Nb, Hf, Zr, Ta, Mo, V, Ti, and W. M may also be selected from one or more of Nb, Hf, Zr, Ta, Mo, V, and W.

[0087] The content of M (a) can satisfy 0 ≤ a ≤ 0.1500 or 0 < a ≤ 0.1500. It can also satisfy 0.0300 ≤ a ≤ 0.1200 or 0.0350 ≤ a ≤ 0.1000.

[0088] The content of B (b) can also satisfy 0 ≤ b ≤ 0.2000. That is, it can also be without B. It can satisfy 0.0500 ≤ b ≤ 0.1400, or it can satisfy 0.0700 ≤ b ≤ 0.1400.

[0089] The content (c) of P can also satisfy 0 ≤ c ≤ 0.2000. That is, it can also be P-free. It can satisfy 0 ≤ c ≤ 0.0700, 0.0001 ≤ c ≤ 0.0700, or 0.0001 ≤ c ≤ 0.0600.

[0090] The Si content (d) can also satisfy 0 ≤ d ≤ 0.2000. That is, it can also be Si-free. It can satisfy 0 ≤ d ≤ 0.1350, 0 ≤ d ≤ 0.0500, or 0 ≤ d ≤ 0.0300.

[0091] The Cu content (e) can satisfy 0 ≤ e ≤ 0.0400 or 0 ≤ e ≤ 0.0300. That is, it can also be Cu-free. It can also satisfy 0.0001 ≤ e ≤ 0.0300, 0.0001 ≤ e ≤ 0.0250, or 0.0001 ≤ e ≤ 0.0200.

[0092] In addition, the soft magnetic alloy of this embodiment can satisfy 0.7000≤1-(a+b+c+d+e)≤0.9000, or 0.7350≤1-(a+b+c+d+e)≤0.8800, or 0.7800≤1-(a+b+c+d+e)≤0.8800.

[0093] In addition, in the soft magnetic alloy of this embodiment, a portion of Fe can be replaced by X1 and / or X2.

[0094] X1 can be one or more selected from Co and Ni. The content of X1 can also be α = 0, meaning it can be completely absent. Alternatively, if the total number of atoms in the composition is set to 100 at%, the number of X1 atoms can be 60 at% or less. That is, it can also satisfy 0 ≤ α{1-(a+b+c+d+e)} ≤ 0.600. Alternatively, it can also satisfy 0 ≤ α{1-(a+b+c+d+e)} ≤ 0.300.

[0095] Especially when X1 is only Co, the ratio of Co content to Fe content can also satisfy 0<α / {1-(α+β)}≤1.000.

[0096] X2 is selected from one or more elements including Al, Mn, Ag, Zn, Sn, As, Sb, Cr, Ga, Bi, N, O, C, S, and rare earth elements. The content of X2 can also be β = 0, meaning it can be absent. Furthermore, if the total number of atoms in the composition is set to 100 at%, the number of X2 atoms can be less than 5.0 at% or less than 3.0 at%. That is, it can satisfy 0 ≤ β{1-(a+b+c+d+e)} ≤ 0.050 or 0 ≤ β{1-(a+b+c+d+e)} ≤ 0.030.

[0097] The range of substitution amounts for Fe to X1 and / or X2 can also be set to less than 70% of Fe in terms of atomic number. That is, it can also be set to 0 ≤ α + β ≤ 0.70.

[0098] Furthermore, the soft magnetic alloy of this embodiment may contain elements other than those included in the main components described above, i.e., elements other than Fe, X1, X2, M, B, P, Si, and Cu, as unavoidable impurities, within a range that does not significantly affect the soft magnetic properties. For example, it may contain 0.1% or less of these elements relative to 100% by mass of the soft magnetic alloy.

[0099] There are no particular restrictions on the shape of soft magnetic alloys. For example, they can be in the form of thin strips or powders.

[0100] The soft magnetic alloy strip in this embodiment is the aforementioned soft magnetic alloy in strip shape.

[0101] The magnetic component of this embodiment has the aforementioned soft magnetic alloy. It may also have the aforementioned soft magnetic alloy strip. Furthermore, the magnetic component may be formed by stacking the aforementioned soft magnetic alloy strip, or it may be formed by winding the aforementioned soft magnetic alloy strip.

[0102] The magnetic component of this embodiment has the aforementioned soft magnetic alloy. It may also have the aforementioned soft magnetic alloy strip. Alternatively, it may be a magnetic component formed by stacking strips of the aforementioned soft magnetic alloy strip that have been broken into smaller pieces. By reducing the size of the aforementioned soft magnetic alloy strip, localized heat generation can be suppressed, thus improving the characteristics of the magnetic component.

[0103] The magnetic component of this embodiment, by incorporating the aforementioned soft magnetic alloy, becomes a magnetic component with improved temperature characteristics, particularly the temperature characteristics related to core loss. In particular, it becomes a magnetic component with improved temperature characteristics related to core loss in the high-frequency domain (100kHz to 1MHz).

[0104] The manufacturing method of the soft magnetic alloy of this embodiment will be described below.

[0105] The manufacturing method of the soft magnetic alloy in this embodiment is not particularly limited; for example, it can be described by using... Figure 3 The apparatus shown is a method for manufacturing soft magnetic alloy strips using a single-roller process.

[0106] In the single-roller process, firstly, pure metals of each metallic element contained in the final soft magnetic alloy are prepared and weighed to achieve the same composition as the final soft magnetic alloy. Then, the pure metals of each metallic element are melted and mixed to create a master alloy. Furthermore, there are no particular limitations on the method of melting the pure metals; for example, a method involving melting by high-frequency heating after evacuating a chamber. Moreover, the master alloy and the final soft magnetic alloy typically have the same composition.

[0107] Next, the prepared master alloy is heated to melt it, resulting in molten metal (liquid). There are no particular restrictions on the temperature of the molten metal; it can be determined by considering factors such as the melting point of the pure metals of each element. For example, it can be set to 1200–1500°C.

[0108] In the single-roller method, molten metal 32 is supplied to a roller 33 rotating in the direction of the arrow, passing through a slit at the bottom of nozzle 31 inside chamber 35. The supplied molten metal 32 is quenched to produce a uniform soft magnetic alloy strip 34. The material of roller 33 is not particularly limited; for example, it can be copper. Furthermore, the thickness of the obtained soft magnetic alloy strip 34 can be adjusted primarily by adjusting the rotational speed of roller 33, and can also be adjusted by adjusting the distance between nozzle 31 and roller 33 or the temperature of molten metal 32. The thickness of the soft magnetic alloy strip 34 is not particularly limited; for example, it can be set to 10–50 μm.

[0109] There are no particular limitations on the temperature of roller 33 or the atmosphere and pressure inside the chamber. For example, the temperature of roller 33 can be set to room temperature to 50°C. The atmosphere inside chamber 35 can be atmospheric or an inert gas atmosphere.

[0110] Next, the obtained soft magnetic alloy strip 34 is subjected to heat treatment. Here, in order to obtain the soft magnetic alloy of this embodiment, it is necessary to appropriately control the heat treatment conditions. Specifically, the heat treatment is performed in at least three stages. In the first stage, the heat treatment is performed at a temperature within the range of a first crystallization temperature Tx1 ± 10°C. The heat treatment temperature in the first stage is set to Tx1 ± 10°C. 1st In the third stage, heat treatment is performed at a temperature lower than the second crystallization temperature Tx2. The heat treatment temperature in the third stage is set to T. 3rd In the second phase, compared to T 1st 10°C or more higher than T 3rd Heat treatment is performed at a temperature 10°C or higher below the required temperature. The heat treatment temperature in the second stage is set to T. 2nd Furthermore, the first crystallization temperature Tx1 is the temperature at which crystallization begins with Fe as the main component, and the second crystallization temperature Tx2 is the temperature at which compounds of Fe and other constituent elements begin to form. Tx1 and Tx2 vary depending on the composition of the soft magnetic alloy strip 34.

[0111] Then, a holding time of 1 to 180 minutes is set for each stage from the first to the third stage. When the total M content is 3.5 at% or more, the holding time can also be 10 to 180 minutes, preferably 30 to 60 minutes. Furthermore, when the M content is low, shortening the holding time easily suppresses the increase in crystallite size. Additionally, the heating rate from room temperature to the first stage, the heating rate between the first and second stages, and the heating rate between the second and third stages are set to 1 to 100 °C / min. When the total M content is 3.5 at% or more, the heating rate is preferably 5 to 50 °C / min. Furthermore, when the M content is low, accelerating the heating rate easily suppresses the increase in crystallite size. Moreover, the heat treatment in each stage from the first to the third stage is performed continuously. That is, cooling to room temperature is not performed between the first and second stages, and between the second and third stages. Additionally, at T... 1st T 2nd and T 3rd It is important to set the heating rate to 0 and maintain the holding time and temperature as described above. If the heating rate is not set to 0 but only reduced, it will be difficult to obtain the soft magnetic alloy strip 34 of this embodiment.

[0112] In the first stage, the main formation is of microcrystal nuclei that become microcrystals. In the second stage, the primary growth of microcrystals occurs, and the microcrystal nuclei transform into microcrystals. In the third stage, the secondary growth of microcrystals occurs. Throughout all stages, heat treatment is performed at temperatures below Tx2, thus making it difficult to crystallize Fe compounds.

[0113] The soft magnetic alloy strip of this embodiment can be obtained through the above methods.

[0114] The magnetic component of this embodiment includes the aforementioned soft magnetic alloy strip. There are no particular limitations on the method for manufacturing the magnetic component comprising the soft magnetic alloy strip. For example, it can be manufactured using commonly employed methods such as stacking soft magnetic alloy strips, winding soft magnetic alloy strips, or stacking miniaturized soft magnetic alloy strips.

[0115] The shape of the soft magnetic alloy in this embodiment is not particularly limited. As described above, a strip shape is exemplified, but powder shape, film shape, block shape, etc. are also considered in addition to the above shape.

[0116] The type of magnetic component in this embodiment is not particularly limited. In particular, magnetic components requiring excellent temperature characteristics for core loss in the high-frequency region can be cited, such as coil components and calendered powder cores. Additionally, reactors, choke coils, and transformers can be cited as coil components. Furthermore, the electronic device of this embodiment includes the aforementioned magnetic components. The type of electronic device is not particularly limited; for example, a DC-DC converter can be cited. Furthermore, the application of the electronic device is not particularly limited; for example, hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and electric vehicles (EVs) can be cited.

[0117] Example

[0118] The present invention will now be described in detail based on specific embodiments.

[0119] (Experimental Example 1)

[0120] In Tables 1 and 3 through 7, raw material metals were weighed to achieve the alloy compositions shown in each table, and melted by high-frequency heating to prepare master alloys. In Table 2, master alloys were prepared such that all samples had the same composition as sample number 1 in Table 1. In Table 8, master alloys were prepared such that all samples had the same composition as sample number 3 in Table 1. Furthermore, the alloy compositions in this embodiment are all those that do not include X1 and X2.

[0121] Then, the master alloy is heated to melt it, and molten metal at 1200-1500°C is produced. The metal is then sprayed onto a roller in the atmosphere using a single-roller method to produce a thin strip.

[0122] X-ray diffraction analysis of the obtained thin bands confirmed that there were no crystals larger than nanocrystals.

[0123] Then, heat treatment was performed under the heat treatment conditions shown in Tables 1 to 8. T was confirmed in all embodiments. 1st Within the range of Tx1±10℃, T 3rd Below Tx2, T 2nd For T 1st 10°C or more higher than T 3rd Temperatures 10°C or higher below. Furthermore, in Tables 1 and 3 through 7, the range from room temperature to T... 1st The rate of heating from T 1st To T 2nd The rate of heating from T 2nd To T 3rd The heating rate was set to 10℃ / minute.

[0124] ICP analysis confirmed that the composition of the heat-treated strip remained unchanged from that of the master alloy.

[0125] X-ray diffraction (XRD) confirmed the presence of α-Fe crystals in each of the heat-treated strips. Further observation was performed using transmission electron microscopy (TEM). In the TEM observations, the magnification was set to 1.00 × 10⁻⁶. 5 ~3.00×10 5 The observation range was set to 128 nm × 128 nm. TEM samples were prepared using FIB with a thickness of 20 nm. The thickness of the TEM samples was confirmed by electron energy loss spectrometry (EELS). Using TEM observations, the total area ratio of the crystallites, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness were calculated. The results are shown in Tables 1–8.

[0126] Then, the temperature characteristics of core loss were evaluated for the magnetic cores fabricated by stacking five thin strips. Specifically, measurements were performed using a BH analyzer (SY8217: manufactured by Iwatsu Measurement & Control) at various temperatures: -30℃, -10℃, 0℃, 10℃, 30℃, 50℃, 80℃, 100℃, 120℃, and 140℃, under the conditions of a measurement frequency of 600kHz and a maximum magnetic flux density of 60mT. Then, for each temperature, the rate of change of core loss from 30℃ was calculated. The absolute value of the rate of change of core loss at which the absolute value of the rate of change of core loss is the maximum rate of change of core loss.

[0127] The following conditions are defined: A+ for the maximum rate of change of core loss below 6.0%; A for 6.0% and below 7.0%; B for 7.0% and below 11.0%; C for 11.0% and below 20.0%; and D for above 20.0%. Conditions A+ to C are defined as good; conditions A+ to B as better; conditions A+ to A as further good; and A+ as the best.

[0128]

[0129] [Table 2]

[0130]

[0131]

[0132]

[0133]

[0134]

[0135]

[0136]

[0137]

[0138] According to Table 1, the total area ratio of the microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness for samples 1a, 2a, 2b, and 1–3 were all within the specified range. As a result, the temperature characteristics of the core loss became good in all samples. The temperature characteristics of the core loss in samples 1, 2, and 2b were particularly good.

[0139] Compared with samples 1, 1a, 2, 2a, and 2b, the temperature characteristics of core loss are worse in sample 3 with a lower M content (a).

[0140] For samples 1, 1a, and 3, a graph showing the rate of change of core loss at a temperature relative to 30°C will be displayed in... Figure 4 As shown in the figure, sample number 1, containing 6.0 at% M and no Si or Cu, showed the highest core loss at 30°C. Sample number 1a, containing 6.0 at% M, 0.5 at% Cu, and no Si, showed that core loss increased with increasing temperature. Sample number 3, containing 3.0 at% M, 1.0 at% Cu, and 13.5 at% Si, showed the lowest core loss at 80°C; however, core loss increased both below and above 80°C.

[0141] Table 2 shows examples and comparative examples where the composition was the same as that of sample 1 but the heat treatment conditions were changed. Samples 1, 4–30, which underwent heat treatment in three stages, all exhibited good temperature characteristics of core loss. Samples 1, 5–30 showed particularly good temperature characteristics of core loss.

[0142] In contrast, in samples 31, 32, and 35–49 that underwent heat treatment in one or two stages, one or more of the following parameters—the total area ratio of microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness—fell outside the specified range. As a result, the temperature characteristics of the magnetic core loss deteriorated.

[0143] Sample No. 34, which underwent three-stage heat treatment but had excessively long holding times in the second and third stages, exhibited an excessively small average thickness of the amorphous phase, leading to deterioration of the temperature characteristics of the magnetic core loss. Additionally, T... 3rd In sample number 33, the total area ratio of microcrystals was too high, which deteriorated the temperature characteristics of the core loss.

[0144] Table 3 shows the embodiments implemented under the same conditions as sample number 1, except that the type of M was changed. Samples 50-57, with the type of M changed, similarly exhibited improved temperature characteristics of core loss as in sample number 1.

[0145] Table 4 shows examples and comparative examples where the composition was the same as that of sample number 1, and the parameters were changed by altering the heat treatment conditions.

[0146] Samples 58, 59, and 6 are examples implemented under the same conditions, except for the holding time in the third stage. The shorter the holding time in the third stage, the lower the total area ratio of the microcrystals, and the greater the average thickness of the amorphous phase and the standard deviation of the thickness of the amorphous phase tend to be.

[0147] Sample numbers 1, 60, 4, and 33 are excluding T. 3rd In addition, there are embodiments and comparative examples implemented under the same conditions. 3rd The lower the value, the lower the total area ratio of the microcrystals, and the greater the average thickness of the amorphous phase and the standard deviation of the thickness of the amorphous phase tend to be.

[0148] Table 5A lists samples 61-70 as examples and comparative examples implemented under the same conditions, except for changes in the content of M (a) and B (b). The higher the content of M and the lower the content of B, the smaller the total area ratio of the microcrystals tends to be. Furthermore, samples 65-69 with an M content of 3.5 at% or more and 10 at% or less exhibit better temperature characteristics of core loss compared to samples 61-64 and 70 with an M content below 3.5 at% or above 10 at%.

[0149] Table 5A lists samples 71-77, which are examples implemented under the same conditions except that the content of M (a) and Fe was changed from sample 1. The higher the M content, the smaller the total area ratio of the microcrystals tends to be. Furthermore, samples 1 and 73-76, with an M content of 3.5 at% or more and 10 at% or less, exhibit better temperature characteristics of core loss compared to samples 71, 72, and 77, with an M content below 3.5 at% or above and above 10 at% or more. Samples 1 and 74-76, with an M content of 4.5 at% or more and 10 at% or less, show particularly good temperature characteristics of core loss.

[0150] Table 5A, Sample numbers 50, 71-2 to 76-2, are examples implemented under the same conditions, except that the type of M was changed from Sample numbers 1, 71 to 76. Table 5A, Sample numbers 51, 71-3 to 76-3, are examples implemented under the same conditions, except that the type of M was changed from Sample numbers 1, 71 to 76. Table 5A, Sample numbers 52, 71-4 to 76-4, are examples implemented under the same conditions, except that the type of M was changed from Sample numbers 1, 71 to 76. Table 5A, Sample numbers 53, 71-5 to 74-5, are examples implemented under the same conditions, except that the type of M was changed from Sample numbers 1, 71 to 74. Table 5B, Sample numbers 54, 71-6 to 74-6, are examples implemented under the same conditions, except that the type of M was changed from Sample numbers 1, 71 to 74. Table 5B's sample numbers 1-7, 71-7 to 74-7 are examples implemented under the same conditions, except that the type of M was changed from sample numbers 1 and 71 to 74. Table 5B's sample numbers 55, 71-8 to 75-8 are examples implemented under the same conditions, except that the type of M was changed from sample numbers 1 and 71 to 75. Table 5B's sample numbers 56, 71-9 to 76-9 are examples implemented under the same conditions, except that the type of M was changed from sample numbers 1 and 71 to 76.

[0151] According to Tables 5A and 5B, even if the type of M is changed, the temperature characteristics of the core loss will remain the same if other conditions are not changed.

[0152] Table 6 shows samples 78-84, which were implemented under the same conditions except that the contents of B (b) and P (c) were changed from sample 67. Samples 67 and 79-83, with a P content greater than 0 and less than 6.0 at%, showed better temperature characteristics of core loss compared to sample 78, which contained no P, and sample 84, which contained more than 6.0 at%.

[0153] Table 6 shows sample numbers 85-91, which are examples implemented under the same conditions except that the P content (c) and Fe content were changed from sample number 1. Sample numbers 1, 86-90, with a P content greater than 0 and less than 6.0 at%, showed better temperature characteristics of core loss compared to sample number 85, which did not contain P, and sample number 91, with a P content exceeding 6.0 at%.

[0154] Table 7 shows the variation of Tx1 with the contents of Fe and Cu, except for sample number 1a. Therefore, Tx1 was changed. 1st In addition, embodiments implemented under the same conditions. The higher the Cu content (e), the smaller the average grain size of the microcrystals tends to be. Moreover, compared with sample number 97c, which has a Cu content of 0 or more and 3.0 at% or less, the sample numbers 1a, 92-97, 96a, 96b, 97a, and 97b have better temperature characteristics of core loss.

[0155] Table 8 shows the examples and comparative examples where the composition was the same as that of sample number 3, but the heat treatment conditions were changed. Among the samples numbered 3, 98 to 120, which underwent heat treatment in three stages, the temperature characteristics of the magnetic core loss were all good.

[0156] In contrast, for samples 121, 122, 124, and 125 that underwent heat treatment in one or two stages, one or more of the following parameters—the total area ratio of microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness—fell outside the specified range. As a result, the temperature characteristics of the magnetic core loss deteriorated.

[0157] Heat treatment is carried out in three stages, but T 3rd In sample number 123, the average thickness of the amorphous phase was too small, which deteriorated the temperature characteristics of the core loss.

[0158] (Experimental Example 2)

[0159] Except for increasing the heating rate and shortening the holding time, the procedure was performed under the same conditions as for sample number 61. The results are shown in Table 9.

[0160]

[0161] According to Table 9, even without M, by appropriately controlling the heat treatment conditions, the total area ratio of the microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness can all be set within the specified range. As a result, even without M, the temperature characteristics of the magnetic core loss are good.

[0162] (Experimental Example 3)

[0163] Except for replacing 1 / 5 of Fe with Co in sample 1a by atomic ratio, samples 127 to 155 were subjected to the same composition as sample 1a. That is, samples 127 to 155 were subjected to the same composition as sample 1a, except that α = 0.2000. Furthermore, samples 127 to 155 were subjected to the heat treatment conditions shown in Table 10. The results are shown in Table 10.

[0164]

[0165] According to Table 10, the temperature characteristics of core loss were good in samples 127-150 that underwent heat treatment in three stages.

[0166] In contrast, for samples 151, 152, 154, and 155 that underwent heat treatment in one or two stages, one or more of the following parameters—the total area ratio of microcrystals, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness—fell outside the specified range. As a result, the temperature characteristics of the magnetic core loss deteriorated.

[0167] Heat treatment is carried out in three stages, but T 3rd In sample number 153, the total area ratio of microcrystals was too high, which deteriorated the temperature characteristics of the core loss.

[0168] Furthermore, compared to sample number 1a which does not contain Co, the embodiments containing Co are able to achieve good temperature characteristics of core loss.

[0169] (Experimental Example 4)

[0170] Except for the change in the Fe and Co content ratio in sample 127, samples 156–166 were performed under the same conditions. The results are shown in Table 11. Furthermore, in sample 1a and samples 127, 156–166, the Ta of sample 1a… 1st The temperature was 460℃, and the samples numbered 127, 156-166 were T. 1st The temperature is 450℃, and the other heat treatment conditions are the same.

[0171]

[0172] According to Table 11, the temperature characteristics of core loss of all specimens numbered 156-166 in Experiment 4 were good.

[0173] Compared with sample number 1a (which does not contain Co) and sample number 165-166 (which contain Co but less than Fe), the sample number 127 and 156-164, which contain Co greater than 0 and Fe less, exhibit better temperature characteristics of core loss.

[0174] (Experimental Example 5)

[0175] Except for the variation in the Fe, Co, and Ni content in sample 127, samples 167 to 175 were performed under the same conditions. The results are shown in Table 12. Furthermore, the heat treatment conditions were the same for all the examples described in Table 12.

[0176]

[0177] According to Table 12, the temperature characteristics of core losses in all samples 167–175, which were reproduced in Experimental Example 5, were excellent. Compared to sample 175, which contained only Ni and no Co, the temperature characteristics of core losses in samples 127 and 167–174 were particularly good.

[0178] (Experimental Example 6)

[0179] Except for changing the content ratio of Fe and X2 and / or the type of X2 in sample number 1a, samples 176 to 228 were performed under the same conditions. The results are shown in Tables 13A to 13D. Furthermore, the heat treatment conditions were the same for all the examples described in Tables 13A to 13D.

[0180]

[0181]

[0182]

[0183]

[0184] According to Tables 13A to 13D, the temperature characteristics of core loss of all specimens 176 to 223 reproduced in Experimental Example 6 were good.

[0185] (Experiment Example 7)

[0186] (Sample numbers 1p-1 and 1p-2)

[0187] The composition obtained is Fe in terms of atomic number ratio. 0.820 Nb 0.060 B0.090 P 0.030 Various raw material metals are weighed separately to form the master alloy. Then, after evacuating the chamber, the master alloy is melted by high-frequency heating.

[0188] Next, the prepared master alloy was heated to melt it, producing a molten metal at 1500°C. The gas heating temperature was set to 30°C, and argon with dew point adjusted was filled into the chamber. The vapor pressure in the chamber was set to 1 hPa, and powder was produced by gas atomization. Furthermore, the resulting soft magnetic metal powder was classified by sieving to achieve an average particle size (D50) of 24 μm.

[0189] Next, the obtained powder was heat-treated under the conditions shown in Table 14.

[0190] The obtained powder was confirmed to contain α-Fe microcrystals by X-ray diffraction (XRD). Further observation was performed using transmission electron microscopy (TEM). In the TEM observation, the magnification was set to 1.00 × 10⁻⁶. 5 ~3.00×10 5 The observation range was set to 128 nm × 128 nm. A TEM sample was prepared using FIB with a thickness of 20 nm. The thickness of the TEM sample was confirmed by electron energy loss spectrometry (EELS). Using TEM observations, the total area ratio of the crystallites, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness were calculated.

[0191] ICP analysis confirmed that the composition of the heat-treated powder remained unchanged from that of the master alloy.

[0192] Next, using the powder of the prepared soft magnetic alloy, a magnetic core (toroidal core) was fabricated. First, the powders were mixed with phenolic resin to form an insulating binder, with the phenolic resin content being 3% by mass of the total. Then, using a standard planetary mixer, the mixture was granulated to a particle size of approximately 500 μm. Finally, the resulting granulated powder was subjected to a surface pressure of 4 ton / cm². 2 The material was molded at 392 MPa to produce a ring-shaped body with an outer diameter of 18 mm, an inner diameter of 10 mm, and a height of 6.0 mm. The resulting body was then cured at 150°C to produce a toroidal magnetic core.

[0193] In addition, the temperature characteristics of core loss were evaluated for the obtained toroidal core. Specifically, measurements were performed using a BH analyzer (SY8217: manufactured by Iwatsu Measurement & Control) at various temperatures of -30℃, -10℃, 0℃, 10℃, 30℃, 50℃, 80℃, 100℃, 120℃, and 140℃, under conditions of a measurement frequency of 600kHz and a maximum magnetic flux density of 60mT. Then, for the core loss at each temperature, the rate of change of core loss from 30℃ was calculated. The absolute value of the rate of change of core loss at which the absolute value of the rate of change of core loss is the largest was defined as the maximum rate of change of core loss. The results are shown in Table 14. Furthermore, the evaluation criteria were the same as in Experimental Example 1.

[0194] For comparison, the results of specimen number 1, which was carried out under substantially the same conditions as specimen number 1p-2 except that the alloy shape was a strip, are shown in Table 14.

[0195] (Sample numbers 127p-1 and 127p-2)

[0196] The composition obtained is (Fe) in terms of atomic ratio. 0.800 C 0.200 ) 0.825 Nb 0.060 B 0.080 P 0.030 Cu 0.005 Various raw material metals are weighed separately to form the master alloy. Then, after evacuating the chamber, the master alloy is produced by melting it through high-frequency heating.

[0197] For sample number 127p-1, subsequent processes, except for T 1st Except for sample number 1p-1, it is the same. For sample number 127p-2, subsequent processes are the same except for T. 1st Except for sample number 1p-2, the results are the same. The results are shown in Table 14.

[0198] For comparison, the results of specimen number 127, which was carried out under substantially the same conditions as specimen number 127p-2 except that the alloy shape was a strip shape, are shown in Table 14.

[0199]

[0200] According to Table 14, in Experiment 7, the heat treatment conditions in samples 1p-1 and 127p-1, which were repeated, were inappropriate. Therefore, the total area ratio of the crystallites, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness were outside the specified range. As a result, the temperature characteristics of the core loss deteriorated. Conversely, in samples 1p-2 and 127p-2, which underwent three stages of heat treatment, appropriate heat treatment was performed. Therefore, the total area ratio of the crystallites, the average thickness of the amorphous phase, and the standard deviation of the amorphous phase thickness were within the specified range. As a result, the temperature characteristics of the core loss improved.

Claims

1. A soft magnetic alloy, wherein, It has a compositional formula in terms of atomic ratio (Fe) (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e)) M a B b P c Si d Cu e The main components of the composition X1 is selected from one or more of Co and Ni. X2 is selected from one or more elements including Al, Mn, Ag, Zn, Sn, As, Sb, Cr, Ga, Bi, N, O, C, S, and rare earth elements. M is selected from one or more of Nb, Hf, Zr, Ta, Mo, V, Ti, and W. 0.0350≤a≤0.1000, 0.0500≤b≤0.1600, 0≤c≤0.0700, 0≤d≤0.0500, 0≤e≤0.0400, 0.7000≤1-(a+b+c+d+e)≤0.8500, 0≤α≤0.6000, 0≤β≤0.0600, 0≤α+β≤0.6000, The soft magnetic alloy comprises microcrystals and an amorphous phase present around the microcrystals. The total area ratio of the microcrystals in the cross-section of the soft magnetic alloy is more than 40% and less than 60%. The average thickness of the amorphous phase is greater than 3.0 nm and less than 10.0 nm, and the standard deviation of the thickness of the amorphous phase is less than 10.0 nm. The content of elements other than those contained in the main component is less than 0.1% by mass relative to 100% by mass of the soft magnetic alloy.

2. The soft magnetic alloy according to claim 1, wherein, The average particle size of the microcrystals is less than 15.0 nm.

3. The soft magnetic alloy according to claim 1 or 2, wherein, The soft magnetic alloy contains P. The content of P is greater than 0 and less than 6.0 at%.

4. The soft magnetic alloy according to claim 1 or 2, wherein, The soft magnetic alloy contains Cu. The Cu content is greater than 0 and less than 3.0 at%.

5. The soft magnetic alloy according to claim 1 or 2, wherein, The soft magnetic alloy contains Co. The Co content is greater than 0 and the Fe content is less than 0.

6. A soft magnetic alloy thin strip, wherein, The soft magnetic alloy comprising any one of claims 1 to 5.

7. A soft magnetic alloy powder, wherein, The soft magnetic alloy comprising any one of claims 1 to 5.

8. A magnetic component, wherein, It is formed by stacking the soft magnetic alloy strips as described in claim 6.

9. A magnetic component, wherein, It is formed by winding the soft magnetic alloy strip as described in claim 6.

10. A magnetic component, wherein, It contains the soft magnetic alloy powder as described in claim 7.

Citation Information

Patent Citations

  • Digital demodulator

    JP1989082718A

  • Soft magnetic material and method for producing same

    CN107949889A

  • Magnetic recording medium and magnetic recording and reproducing device

    JP2006079757A